Приводимость линейных систем разностных уравнений с почти периодическими коэффициентами - Митропольський, Ю.А.; Мартынюк, Д.И.; Тынный, В.И. (Український математичний журнал, 1993)
We establish sufficient conditions of the reducibility of the linear system of difference equations x(t+1)=Ax(t) + P(t) x(t) with an almost periodic matrix P(t) to a system with a constant matrix.